2016
DOI: 10.1002/ange.201603882
|View full text |Cite
|
Sign up to set email alerts
|

Didehydroaspartate Modification in Methyl‐Coenzyme M Reductase Catalyzing Methane Formation

Abstract: All methanogenic and methanotrophic archaea known to date contain methyl‐coenzyme M reductase (MCR) that catalyzes the reversible reduction of methyl‐coenzyme M to methane. This enzyme contains the nickel porphinoid F430 as a prosthetic group and, highly conserved, a thioglycine and four methylated amino acid residues near the active site. We describe herein the presence of a novel post‐translationally modified amino acid, didehydroaspartate, adjacent to the thioglycine as revealed by mass spectrometry and hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…A suite of interesting, enzymatically installed bbPTMs has been discovered in archaeal methyl-coenzyme M reductase, a key enzyme in methane metabolism (Figure 3d). 23−25 Didehydroaspartate, 25 α-methylglutamine, 24 and thioglycine 24 (substitution of the carbonyl oxygen of a glycine residue with a sulfur atom) have been detected in several homologues near the 29 and by protein isoaspartate methyltransferase (PIMT), 30 respectively. (b) Proposed mechanism 13,27 for thioamide formation in methyl-coenzyme M reductase via a kinase that targets the backbone amide, YcaO, and an auxiliary protein of unknown function, TfuA, which may be involved in substrate recognition or sulfur transfer.…”
Section: ■ Protein Backbone Modifications Modulate Protein Activity A...mentioning
confidence: 99%
See 2 more Smart Citations
“…A suite of interesting, enzymatically installed bbPTMs has been discovered in archaeal methyl-coenzyme M reductase, a key enzyme in methane metabolism (Figure 3d). 23−25 Didehydroaspartate, 25 α-methylglutamine, 24 and thioglycine 24 (substitution of the carbonyl oxygen of a glycine residue with a sulfur atom) have been detected in several homologues near the 29 and by protein isoaspartate methyltransferase (PIMT), 30 respectively. (b) Proposed mechanism 13,27 for thioamide formation in methyl-coenzyme M reductase via a kinase that targets the backbone amide, YcaO, and an auxiliary protein of unknown function, TfuA, which may be involved in substrate recognition or sulfur transfer.…”
Section: ■ Protein Backbone Modifications Modulate Protein Activity A...mentioning
confidence: 99%
“…active site, attesting to their importance. A candidate oxidoreductase for didehydroaspartate formation has been postulated, 25 and it has been demonstrated that the C α -methyl group of α-methylglutamine originates from the cofactor Sadenosylmethionine, but a specific methyltransferase has not been identified. 26 Recently, the enzymes responsible for thioglycine formation, a backbone kinase (YcaO) and an auxiliary protein of unknown function (TfuA), have been identified through homologues involved in natural product thioamide biosynthesis pathways (Figure 4a).…”
Section: ■ Protein Backbone Modifications Modulate Protein Activity A...mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore,M CR contains many modified amino acids near the active site,namley,four methylated amino acids,d idehydroaspartate, [9] and thioglycine,t he main-chain carbonyl oxygen of which is exchanged with sulfur. Fore xample,t he crystal structure of the active MCR red1 form has to be solved.…”
mentioning
confidence: 99%
“…To date, all proposed mechanisms are based on crystal structures of the inactive forms of MCR. Furthermore,M CR contains many modified amino acids near the active site,namley,four methylated amino acids,d idehydroaspartate, [9] and thioglycine,t he main-chain carbonyl oxygen of which is exchanged with sulfur. [10] Thec atalytic mechanism should explain why these modifications are present.…”
mentioning
confidence: 99%